Halitosis And Its Associated Factors Among Kermanshah High School Students (2015) - Ziaei N; Hosseinpour S; Nazari H; Rezaei M; Rezaei K (Dove Medical Press, 2019)
Narges Ziaei,1 Sajjad Hosseinpour,1 Hesamedin Nazari,2 Mansour Rezaei,3 Khansa Rezaei4 1Department of Periodontology, School of Dentistry, Kermanshah University of Medical Sciences, Kermanshah, Iran; 2Department of Oral and Maxillofacial Surgery, School of Dentistry, Kermanshah University of Medical Sciences, Kermanshah, Iran; 3Social Development and Health Promotion Research Center, Kermanshah University of Medical Sciences, Kermanshah, Iran; 4Educational Development Center, Kermanshah University of Medical Sciences, Kermanshah, IranCorrespondence: Khansa RezaeiEducational Development Center, Taleghani Hospital, Shahid Beheshti Blvd, Kermanshah 67146-73159, IranTel +989189333405Email khansarezaei@gmail.comIntroduction: Halitosis as a common dental problem results in psychological social problems and relates to many factors. The aim of this study was to evaluate the prevalence of halitosis and its associated factors among students aged from 14 to 18 years in Kermanshah in 2015.Materials and methods: The study was conducted in high school students of Kermanshah city in 2015. The questionnaire including questions about bad breath and other associated factors (demographic information, background diseases, oral and dental problems, decay-missing-filled (DMF) index, etc.) was completed by students or determined by the examiner. Organoleptic evaluation was conducted. Prevalence of organoleptic and self-reported halitosis and related factors was reported. The relationship between malodor and variables was evaluated and the most important factor was determined by multiple logistic regression analysis. The diagnostic agreement between self-perception and organoleptic halitosis was assessed using Kappa coefficient as well.Results: The prevalence of halitosis in the organoleptic evaluation was 29.75% and higher in boys (32.6% male vs. 25.2% female) and 27.47% in self-perception (32.9% male vs. 19% female). The diagnostic agreement between organoleptic and self-perception halitosis was moderate or poor. Among the studied factors, the most important factor related to the organoleptic evaluation of halitosis was DMF≥4 (P<0.001 and OR=2.253).Conclusion: The DMF index was the factor most strongly associated with organoleptic halitosis in this sample of high school students. Other factors with significant association included parent’s lower education level, not brushing, not flossing, bleeding gums, tongue coating, pericoronitis, and plaque index. Also, older age, male gender, and gastrointestinal disease increased the possibility for halitosis.Keywords: halitosis, organoleptic, self-perception